The The Mediating Role of Competence on the Effect of Organizational Culture and Readiness To Change on Organizational Entrepreneurship - Dyah Pikanthi Diwanti (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2023)
Background – An increasingly dynamic environment keeps the organization moving. To stay relevant, it is necessary to support readiness for change, especially related to the Human Resources (HR) competence. The sustainability of an organization is influenced by independence through entrepreneurial activities to contribute to independent funds Research purposes – This research aims to determine how readiness to change runs in organizational culture for human resources by improving organizational entrepreneurship competencies Design/ Methodology/ Approach – This study applied quantitative research with survey techniques and SEM AMOS analysis tools. Statements were distributed using a Likert scale of 1-5. Based on the results of the validity and reliability test, it was declared valid and reliable. Before testing the hypothesis with a structural model, a model suitability test (Fit) based on data processing was carried out using the SEM-AMOS analysis tool. Results and Discussion – 1) Organizational culture has a significant effect on Organizational Entrepreneurship. 2) Organizational culture has a significant effect on competence. 3) Organizational culture positively affects organizational entrepreneurship with Competence as a mediator variable. 4) Readiness to change does not have a positive effect on organizational entrepreneurship. 5) Readiness to change in HR has a positive effect on competence. 6) Readiness to change has a positive effect on organizational entrepreneurship with competence as a mediator variable. 7) Competence has a positive effect on organizational entrepreneurship. Conclusion – The influence of readiness for change in human resources on organizational entrepreneurship with competence as a mediator variable resulted in significant and positive results of the influence of independent variables on the dependent variable with human resource competence as a mediator variable. Research implications – This research provides knowledge to readers/business actors/stakeholders that the readiness to change human resources towards organizational entrepreneurship with competency as the moderator variable has a significant influence. Research limitations – This research discusses the mediating role of competence on the effect of organizations and readiness to change on organizational entrepreneurship